1998
DOI: 10.1007/pl00007588
|View full text |Cite
|
Sign up to set email alerts
|

Guinea Pig Pulmonary Mechanics: Altered Sensitivity to Carbachol by Cadmium and/or Selenium

Abstract: Male Hartley guinea pigs (480-610 g) were treated intratracheally as follows: saline, cadmium (Cd, 0.3 mg), selenium (Se, 0.3 or 0.06 mg), or Se (0.06 mg) and Cd (0.3 mg) simultaneously. Selenium and Cd were administered as sodium selenite and cadmium chloride, respectively. Twenty-four h later, dynamic lung compliance (Cdyn) and pulmonary resistance (Rp) were measured before (baseline Cdyn and Rp) and after carbachol administration (0.0001, 0.001, 0.01, and 0.1 mumol/kg, intravenously). Results indicated a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In a recent study, we have characterized by light microscopy the DMSe-induced lesions observed in trachea and lungs of treated mice (Cherdwongcharoensuk et al, 2003). The current investigation offers a rationale for the pathology that we and others have reported in respiratory tissues after DMSe instillation (Bell et al, 1997(Bell et al, , 1998Nonavinakere et al, 1999, Cherdwongcharoensuk et al, 2003. In fact, the present observations indicate that inflammatory neutrophils and macrophages are likely mediators of the alterations caused in respiratory tissues by the presence of Se in the airways.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a recent study, we have characterized by light microscopy the DMSe-induced lesions observed in trachea and lungs of treated mice (Cherdwongcharoensuk et al, 2003). The current investigation offers a rationale for the pathology that we and others have reported in respiratory tissues after DMSe instillation (Bell et al, 1997(Bell et al, , 1998Nonavinakere et al, 1999, Cherdwongcharoensuk et al, 2003. In fact, the present observations indicate that inflammatory neutrophils and macrophages are likely mediators of the alterations caused in respiratory tissues by the presence of Se in the airways.…”
Section: Discussionsupporting
confidence: 59%
“…Most of the studies on the toxicology of selenium (Se) have used oral ingestion (Nantel et al, 1985;Pentel et al, 1985;Köppel et al, 1986;Matoba et al, 1986;Gasmi et al, 1997). Only a few investigations have documented that Se inhalation is harmful for the airways and lungs (Bell et al, 1997a(Bell et al, , 1997b(Bell et al, , 1998Nonavinakere et al, 1999;Cherdwongcharoensuk et al, 2003). Human exposure to airborne Se may occur accidentally from several industrial activities.…”
Section: Discussionmentioning
confidence: 99%